Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd006119.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of follow-up strategies for patients with epithelial ovarian cancer following completion of primary treatment

Abstract: Background Ovarian cancer is the sixth most common cancer and seventh cause of cancer death in women worldwide. Traditionally, many patients who have been treated for cancer undergo long-term follow up in secondary care. Recently however it has been suggested that the use of routine review may not be effective in improving survival, quality of life (QoL), and relieving anxiety. In addition, it may not be cost effective. Objectives To compare the potential benefits of different strategies of follow up in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This discordance between the two studies may be due to the different assay methods used for detecting sFRA, the size of our larger study or due to different patient populations, or a combination thereof. Our study demonstrated that sFRA levels were not elevated in ovarian metastasis from the colorectal cancer patients or endometriotic cysts which often exhibited elevated CA125, further indicating the specificity for sFRA in EOC. However, given the limited sample size for the metastasis from other tumors in this study, these data should be interpreted with caution but warrant further study.…”
Section: Discussionmentioning
confidence: 57%
“…This discordance between the two studies may be due to the different assay methods used for detecting sFRA, the size of our larger study or due to different patient populations, or a combination thereof. Our study demonstrated that sFRA levels were not elevated in ovarian metastasis from the colorectal cancer patients or endometriotic cysts which often exhibited elevated CA125, further indicating the specificity for sFRA in EOC. However, given the limited sample size for the metastasis from other tumors in this study, these data should be interpreted with caution but warrant further study.…”
Section: Discussionmentioning
confidence: 57%
“…These biological or ‘chemical ‘ recurrence patients frequently have small-volume disease on surgical investigation; however, the value of treatment in the absence of symptoms has been strongly challenged. 55 A recent phase III study examined the role and impact of serial CA-125 surveillance. 56 In this study, 1,442 women in complete clinical remission following front-line therapy underwent CA-125 evaluation every 3 months.…”
Section: Recurrent Therapymentioning
confidence: 99%
“…The reported aim of regular follow-up is to allow detection of recurrent disease before symptoms develop, allowing earlier treatment with a possible improved outcome, as well as providing an opportunity to provide information and signal early and late consequences of treatment. For follow-up to be effective in this context, the management of recurrence must be amenable to an intervention which itself leads to an improved survival [10]. However, for many cancers, recurrences are not commonly identified in asymptomatic patients at follow-up consultations and most recurrences are reported as interval events [11].…”
Section: Routine Follow-up In Oncology Practicementioning
confidence: 99%